Spectrum of Muscle Histopathologic Findings in Forty‐Two Scleroderma Patients With Weakness. Issue 10 (October 2015) - Paik, Julie J.; Wigley, Fredrick M.; Lloyd, Thomas E.; Corse, Andrea M.; Casciola‐Rosen, Livia; Shah, Ami A.; Boin, Francesco; Hummers, Laura K.; Mammen, Andrew L.
<x xml:space="preserve">Abstract</x> Objective To determine if distinct muscle pathologic features exist in scleroderma subjects with weakness. Methods This retrospective study included weak scleroderma subjects with muscle biopsies available for review. Biopsies were systematically assessed for individual pathologic features, including inflammation, necrosis, fibrosis, and acute neurogenic atrophy. Based on the aggregate individual features, biopsies were assigned a histopathologic category of polymyositis, dermatomyositis, necrotizing myopathy, nonspecific myositis, "acute denervation, " "fibrosis only, " or "other." Clinical data analyzed included autoantibody profiles, scleroderma subtype and disease duration, Medsger muscle severity scores, creatine kinase, electromyography, and muscle magnetic resonance imaging. Results A total of 42 subjects (79% female and 64% diffuse scleroderma) were included in this study. Necrosis (67%), inflammation (48%), acute neurogenic atrophy (48%), and fibrosis (33%) were the most prevalent pathologic features. The presence of fibrosis was strongly associated with anti–PM‐Scl antibodies. Histopathologic categories included nonspecific myositis (36%), necrotizing myopathy (21%), dermatomyositis (7%), "acute denervation" (7%), "fibrosis only" (7%), and polymyositis (5%). Disease duration of scleroderma at the time of muscle biopsy was shorter in polymyositis than other histopathologic categories. Patients with anti–PM‐Scl and Scl‐70 antibodies also had a shorter disease duration than those with other autoantibody profiles. Conclusion Nonspecific myositis and necrotizing myopathy were the most common histopathologic categories in weak scleroderma subjects. Surprisingly, nearly half of the subjects studied had histologic evidence of acute motor denervation (acute neurogenic atrophy); this has not been previously reported. Taken together, these observations suggest that a variety of pathologic mechanisms may underlie the development of myopathy in scleroderma.